An Analysis of L2 Stress Patterns of Polysyllabic Academic Vocabulary of Indonesian Students - Yana, Wayan Karang (Universitas Islam Negeri Raden Intan Lampung, 2017)
This research project explores the production of stress placement on polysyllabic academic words of Indonesian students studying at Coventry University, United Kingdom. The research adopts qualitative approach and looks at the accuracy of the stress placement on polysyllabic academic vocabulary produced by the students. The participants of the research are seven Indonesian students studying at Coventry University where they have been studying English for approximately more than ten years. The participants are interviewed and recorded in a silent room in order to obtain a good quality recording. There are three parts of the interview in the research, which consist of free speaking, text-reading and another free speaking about students’ opinion. The results are drawn from the recordings by analysing and rating the accuracy of stress placement on the polysyllabic academic words. In addition, it is also rated by a co-rater who is a native speaker and has adequate knowledge on English phonology, to verify the validity and the reliability of the results. The conclusion drawn from the findings is that most participants tend to avoid using academic vocabulary in their presentation based on the first interview and have the tendency of not stressing the words and even misplacing the stress due to ignorance of stress pattern in English. The result indicates that the student’s encounter is due to the interference of their mother language as Bahasa is a syllable-timed language meanwhile English is a stress-timed one, which therefore causes significant interference in their stress placement. It is also concluded that the length of exposure of English use in their previous institution can be accountable variable for the accuracy of their stress placement production.